ANALISIS IMPULSE BUYING DALAM BERBELANJA ONLINE (Studi Pada Mahasiswa STIE Gentiaras Bandar Lampung) - Yunada Arpan; Stephani Dwi Lingga Ambarwati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Impulse buying is an irrational purchase and is associated with quick and unplanned purchases,followed by a conflict of thoughts and emotional impulses. Impulse buying does not only happen inoffline purchases (in-store), but can also occur when consumers do shopping online. This study aims todetermine the internal faktors and external faktors to impulse buying in online shopping. The subjects ofthis study were STIE Gentiaras Bandar Lampung students who had done impulse buying during onlineshopping.The results of this study are internal faktors and external faktors together - positive to impulsebuying in online shopping. The comparison of online purchase cost is insignificant and insignificant tothe impulse buying variable in online shopping. The definition of determination test (R2) shows thedetermination of 69.2%.